THE CLASSIFICATION OF PROMOTION MEDIA OF A COLLEGE TO IMPROVE THE MANAGEMENT OF PROMOTION FOR A PRIVATE COLLEGE IN THE EAST OGAN KOMERING ULU DISTRICT - Graika Garaika; Gaeldeba Garaika (Jurnal TAM (Technology Acceptance Model), 2020)
Educational institutions are strategic sectors that can produce quality human resources where educational institutions take place quickly and dynamically. The development and progress of an educational institution are very dependent on the human resources that manage the institution. Promotion media is very important for the progress of an educational institution.  Promotion media is means used to introduce and communicate a product or brand to be known to the wider public. There are three categories of promotional media namely print media, electronic media, and online media. Based on the 2018 BPS, those interested in print and electronic media as a source of information were 25.53% while for online media in 2019 there were 64.8%. So that promotions can be carried out appropriately according to regional conditions, it is necessary to classify promotional media by region. This study aims to classify promotional media according to the region using the C45 algorithm method. The C45 algorithm is used as a decision tree classification model to predict promotional media that is suitable for the promotional target area. To form a decision tree, attributes needed are used as a reference for classification, in this study six attributes are used, namely the availability of internet services, the availability of electricity services, community work, community income, education, and access from the region to the district government.